2010
DOI: 10.1021/jf904401j
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Relationships among Active Components in Black Raspberry (Rubus occidentalis L.) Fruit Extracts Using High-Resolution 1H Nuclear Magnetic Resonance (NMR) Spectroscopy and Multivariate Statistical Analysis

Abstract: A process was developed to ascertain the bioactive components of black raspberry (Rubus occidentalis L.) fruit extracts by relating chemical constituents determined by high-field nuclear magnetic resonance (NMR) spectroscopy to biological responses using partial least-squares regression analysis. To validate our approach, we outlined relationships between phenolic signals in NMR spectra and chemical data for total monomeric anthocyanin (TMA) content and antioxidant capacity by the ferric-reducing antioxidant p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
31
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 43 publications
3
31
0
Order By: Relevance
“…Cyanidin-3-xylosylrutinoside and cyanidin-3-rutinoside were the major anthocyanins, comprising roughly 90% of the sum of the individual anthocyanins (Table 1). This agrees with other studies indicating that these two anthocyanins comprise the majority of anthocyanins present in black raspberry (Tian et al, 2006;Tulio et al, 2008;Wyzgoski et al, 2010). These two main anthocyanins were also more potent phenolic antioxidants (cyanidin-3-xylosylrutinoside > cyanidin-3-rutinoside) compared to the other anthocyanins present in black raspberry fruit , although it was not clear in this study if the individual anthocyanins antioxidant activities were compared on an equal molar or equal weight basis.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…Cyanidin-3-xylosylrutinoside and cyanidin-3-rutinoside were the major anthocyanins, comprising roughly 90% of the sum of the individual anthocyanins (Table 1). This agrees with other studies indicating that these two anthocyanins comprise the majority of anthocyanins present in black raspberry (Tian et al, 2006;Tulio et al, 2008;Wyzgoski et al, 2010). These two main anthocyanins were also more potent phenolic antioxidants (cyanidin-3-xylosylrutinoside > cyanidin-3-rutinoside) compared to the other anthocyanins present in black raspberry fruit , although it was not clear in this study if the individual anthocyanins antioxidant activities were compared on an equal molar or equal weight basis.…”
Section: Resultssupporting
confidence: 89%
“…Total anthocyanins by HPLC in this study were somewhat lower than reported by Wu et al (2006), 687 mg 100 g À1 (n = 1; cultivar unknown), and Hager et al (2008), 1113 mg 100 g À1 (n = 1; 'Munger'). Six individual anthocyanins (cyanidin-3-sambubioside, cyanidin-3-glucoside, cyanidin-3-xylosylrutinoside, cyanidin-3-rutinoside, pelargonidin-3-rutinoside, and peonidin-3-rutinoside; in the order of elution) were detected in juice from the populations in this study as previously reported (Dossett et al, 2008;Hong & Wrolstad, 1990;Tulio et al, 2008;Wu et al, 2006;Wyzgoski et al, 2010). Refer to Dossett et al (2008) for a representative black raspberry chromatogram analyzed under these sample preparation and HPLC conditions.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…Studies characterizing the types of anthocyanins present in black raspberry fruit date back to at least the 1960s (Nybom, 1968). A number of recent studies have examined the anthocyanin composition of black raspberry fruit using more sophisticated tools than those available 50 years ago and have consistently detected cyanidin-3-glucoside, cyanidin-3-sambubioside, cyanidin-3-rutinoside, cyanidin-3-xylosylrutinoside, pelargonidin-3-rutinoside, and peonidin-3-rutinoside (Dossett, Lee, & Finn, 2008;Tian, Giusti, Stoner, & Schwartz, 2006a, 2006bTulio et al, 2008;Wyzgoski et al, 2010). Wu, Pittman III, and Prior (2006) also found trace levels of pelargonidin-3-glucoside in black raspberry fruit.…”
Section: Introductionmentioning
confidence: 99%